Troubling Talk: A Politics and History of Indistinction in the Upper Sorbian Community - Spreng, Elizabeth (Slavia Centralis, 2020)
The article focused on the cultural processes that affect speakers of Upper Sorbian, an endangered Slavic community in Eastern Germany. Through an anthropological approach, language choices emerge as a complex negotiation of linguistic identity evidenced in critique of other Sorbs and language use as well as choosing to distance oneself from the community.
Keywords: language endangerment; globalization; ethnography